1996
DOI: 10.1074/jbc.271.25.15002
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-1β and Glutamate Activate the NF-κB/Rel Binding Site from the Regulatory Region of the Amyloid Precursor Protein Gene in Primary Neuronal Cultures

Abstract: We originally reported that members of the family of transcription factors NF-B/Rel can specifically recognize two identical sequences, referred to as APP B sites, which are present in the 5 -regulatory region of the APP gene. Here we show that the APP B sites interact specifically with a complex which contains one of the subunits of the family, defined as p50 protein, and that they act as positive modulators of gene transcription in cells of neural origin. Additionally, the nuclear complex specifically bindin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
87
0
2

Year Published

1997
1997
2015
2015

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 143 publications
(92 citation statements)
references
References 45 publications
2
87
0
2
Order By: Relevance
“…Each patient was given two sets of similar questions before and after surgery, and 10 cases of normal cases formed the control group. The Z scoring method was used to exclude the effect of any learning effects caused by the short-term repeat of two tests (Grilli et al, 1996;Kienlen-Campard et al, 2000;Townsend et al, 2002). The experimental results showed that the two groups of patients with or without POCD had no obvious differences in cognitive functions before the operation.…”
Section: Discussionmentioning
confidence: 98%
“…Each patient was given two sets of similar questions before and after surgery, and 10 cases of normal cases formed the control group. The Z scoring method was used to exclude the effect of any learning effects caused by the short-term repeat of two tests (Grilli et al, 1996;Kienlen-Campard et al, 2000;Townsend et al, 2002). The experimental results showed that the two groups of patients with or without POCD had no obvious differences in cognitive functions before the operation.…”
Section: Discussionmentioning
confidence: 98%
“…66 The amyloid precursor protein (APP) gene has a kB regulatory site. 67 Thus, overexpression of aPKC might directly stimulate transcription of APP through a kB-dependent pathway resulting in accumulation of excess secretory APP in the media. In this manner, secretory APP (sAPP) acting in an autocrine fashion could promote survival through an NF-kB dependent pathway.…”
Section: Discussionmentioning
confidence: 99%
“…79 In addition, NF-kB might also play a role in amyloidogenesis itself, since expression of APP can be induced by NF-kB. 80 Mutations in the genes encoding APP, presenilin-1, and presenilin-2 cause inherited early-onset Alzheimer's disease. The presenilins are essential for cleavage of APP at the C-terminus of amyloid b-peptide, the final step in amyloid b-peptide production.…”
Section: Chronic Neurodegenerative Disordersmentioning
confidence: 99%